Acetochlor Affects Bighead Carp (Aristichthys Nobilis) by Producing Oxidative Stress, Lowering Tissue Proteins, and Inducing Genotoxicity. (23rd May 2022) - Mahmood, Yasir; Hussain, Riaz; Ghaffar, Abdul; Ali, Farah; Nawaz, Sadia; Mehmood, Khalid; Khan, Ahrar
Abstract : Acetochlor is persistently used in the agroproduction sector to control broadleaf weeds. Due to frequent and continuous applications, this herbicide can reach nearby water bodies and may induce deleterious changes in aquatic life. Therefore, investigation of harmful impacts of different environmental pollutants, including herbicides, is vital to knowing the mechanisms of toxicity and devising control strategies. The current experiment included bighead carp (n = 80 ) to estimate adverse impacts. Fish were randomly placed in 4 different experimental groups (T0-T3) and were treated for 36 days with acetochlor at 0, 300, 400, and 500 μ g/L. Fresh blood without any anticoagulant was obtained and processed for nuclear and morphological changes in erythrocytes. At the same time, various visceral organs, including the gills, liver, brain, and kidneys, were removed and processed on days 12, 24, and 36 to determine oxidative stress and various antioxidant biomarkers. Comet assays revealed significantly increased DNA damage in isolated cells of the liver, kidneys, brain, and gills of treated fish. We recorded increased morphological and nuclear changes (P ≤ 0.05 ) in the erythrocyte of treated fish. The results on oxidative stress showed a higher quantity of oxidative biomarkers and a significantly (P ≤ 0.05 ) low concentration of cellular proteins in the gills, liver, brain, and kidneys of treated fish compared to unexposed fish. Our research findings concluded that acetochlor renders oxidative stress in bighead carp.